If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -1) = 3 + 3x Reorder the terms: 3(-1 + x) = 3 + 3x (-1 * 3 + x * 3) = 3 + 3x (-3 + 3x) = 3 + 3x Add '-3x' to each side of the equation. -3 + 3x + -3x = 3 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + 0 = 3 + 3x + -3x -3 = 3 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 = 3 + 0 -3 = 3 Solving -3 = 3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -3=5-4c | | 8/7x+2=-3 | | 2r-2=-7(8+r) | | 7(2x-3)=12x-5 | | a-(-6)=-18 | | 0=4t^2-10t+13 | | 4x-2x-4=12 | | 2x-1*3x-4= | | -7(3x+6)/=7 | | 25/16x2 | | 5x+2=-48 | | 6=(24x+6) | | 0.04(y-4)+0.12y=0.02y-1 | | 2x+8x+10=60 | | -29=-c/9 | | 2x25/16 | | 45-33=12+y/-5 | | 14x-19=(52x)-95 | | x+3x+4=24 | | 3(x+1)-4(y-1)=13 | | (4x-7)/4 | | -.08x-.19=-.12x+.11 | | 4xy+7xy+6xsquaredy+7xysquared= | | 2(x-3)+2x=4(x+6)-30 | | 4xy+7xy+6xsquaredy+7xysquared= | | 4(-7+5q)= | | 10x+5x+15=60 | | 7(x-8)=2(x+22)+940 | | 3[7-2(-4-1)]= | | -8x-8+3(x-2)=3x+2 | | 1/3(6h+15) | | 3(k+8)=5k+8-2k |